Estimation of diffusion coefficients during carrots cooking in arsenious solution at different temperatures - Galvez, Oscar Daniel (2024)
This study is based on an investigation of the transport phenomenon, specifically the quantification of arsenic diffusion in carrots within a temperature range of 89 °C–99 °C using a thin plate model. Studying the diffusion of arsenic in carrots is important due to its toxicity, as it can concentrate during cooking. The World Health Organization considers arsenic as one of the ten chemical substances of public health concern. In this study, biennial hybrid carrots of the Nantesa variety were cooked whole with their epidermis in an aqueous solution containing diarsenic trioxide with an As concentration of 5 mgL−1 at 89 °C, 94 °C, and 99 °C. The cooking times of the carrots at different temperatures were based on a specific degree of tenderness, with a value of ≤3 kg m−2. The evaluated data showed consistency with increasing temperature. The calculated effective diffusion coefficients at temperatures of 89 °C, 94 °C, and 99 °C were 5.84E-09 m2s-1, 1.08E-08 m2s-1, and 2.51E-08 m2s-1 for the flesh (DL), and 1.601E-11 m2s-1, 2.15E-11 m2s-1, and 4.39E-11 m2s-1 for the epidermis (DE), respectively. The activation energy for diffusion was determined to be 159.54 kJmol−1 for the and 110.68 kJmol−1 for the epidermis. Similar behaviours were observed in different radial positions of the carrot, where the arsenic content decreased from the periphery to the centre, consistent with studies on diffusion phenomena with other solutes in food. The novelty was the detailed quantification of arsenic diffusion in the Nantes-type hybrid carrot matrix. This study is limited to a specific concentration of 5 mgL−1 of arsenic solution. The findings of this study may have significant implications for public health and food safety.